IMMUNOLOGICAL CAUSES OF METABOLIC SYNDROME - Скрипник, Н. В. (PRECARPATHIAN BULLETIN OF THE SHEVCHENKO SCIENTIFIC SOCIETY Pulse, 2019)
The article presents data from publications and the author’s personal research findings that generalize peculiarities of immunological status of patients with diabetes mellitus with syndrome of disordered metabolism. Evidence is given that immune-mediated pathological changes depend on the seriousness and durability of the disease and serve as a predictive criterion of evolving complications caused by type 2 diabetes mellitus. It is concluded that type 2 diabetes mellitus may result in two possible immune-mediated pathological disorders: variant 1 – dysfunctions of cell-mediated immunity, phagocytosis with compensatory hyperactive response of the humoral (component of the) immune system; variant 2 – cell suppression, phagocytic disorders and suppression of the humoral component which either corresponds to or proceeds the phase of suppurative complications necrotic; unfavourable for clinical treatment of type 2 diabetes mellitus. Available findings appear to be sufficient to indicate that immune therapy is not only desirable but pathogenetically proved as typically needed and promising strategies to prevent evolving diabetes-specific complications and improve the risk profile of the chronic complications as the disease progresses.